Preparation method of flexible transparent conductive electrode based on PEDOT:PSS and application thereof

CN122968038APending Publication Date: 2026-10-23SHANGHAI ASTRACE NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611275202.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

为提高导电层与柔性基材之间的结合强度和耐弯折性,通常需要增加柔性成膜组分和交联组分,而上述组分可能影响PEDOT导电网络的连续性;为降低方阻而增加导电增强剂时,又难以兼顾导电层的成膜稳定性和基材结合性能

Benefits of technology

1.本发明分别配制第一电极涂布液和第二电极涂布液,使第一电极涂布液具有较高的柔性成膜组分和交联组分含量,使第二电极涂布液具有较高的极性导电增强剂含量,由此在同一复合导电层中形成柔性锚固区和导电匹配区。柔性锚固区提高复合导电层与柔性透明基材之间的结合稳定性并承受弯曲变形,导电匹配区保持PEDOT导电网络的连续性,从而减少单一配方同时承担不同性能要求时产生的相互制约。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of transparent conductive films, and discloses a preparation method of a flexible transparent conductive electrode based on PEDOT:PSS and application thereof, which comprises the following steps: activating a flexible transparent base material; preparing a first electrode coating liquid and a second electrode coating liquid, the content of flexible film-forming components and cross-linking components of the first electrode coating liquid is relatively high, and the content of a polar conductive enhancer of the second electrode coating liquid is relatively high; sequentially performing wet-on-wet coating to form a composite wet film with an interlayer mutual diffusion zone; and performing pre-drying, thermal cross-linking and roller flattening to form a composite conductive layer with a flexible anchoring zone, a composition transition zone and a conductive matching zone. The obtained electrode is used for liquid crystal dimming films and curved glass. The application allocates the requirements of base material combination, bending resistance, conductivity and refractive index matching to different areas, and connects the areas with a composition transition zone, so that the problem that a homogeneous conductive layer is difficult to simultaneously consider adhesion stability, conductivity and low reflection performance is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of transparent conductive film technology, and more specifically, to a method for preparing flexible transparent conductive electrodes based on PEDOT:PSS and their applications. Background Technology

[0002] Transparent conductive electrodes possess both light transmittance and electrical conductivity, making them widely used in optoelectronic devices such as liquid crystal dimming films, flexible displays, and smart glass. Existing transparent conductive electrodes typically employ an indium tin oxide (ITO) conductive layer. While ITO exhibits good conductivity and visible light transmittance, it is an inorganic, brittle material prone to microcracks when bent on flexible substrates or bonded to curved glass, leading to increased local resistance or conductive failure. PEDOT:PSS, with its water dispersibility, solution processability, and flexibility, can form a transparent conductive layer on polymer substrates through coating, and is therefore increasingly being used in flexible transparent electrodes.

[0003] Chinese patent application CN107817618A discloses a smart dimming film, which involves coating a PEDOT:PSS dispersion onto a transparent PET film and baking it to form a transparent conductive layer, with a polymer-liquid crystal mixture layer placed between the two transparent conductive layers. This solution realizes the application of PEDOT:PSS in dimming films, but its conductive layer uses a uniformly composed PEDOT:PSS coating. To improve the bonding strength and bending resistance between the conductive layer and the flexible substrate, it is usually necessary to increase the flexible film-forming components and crosslinking components. However, these components may affect the continuity of the PEDOT conductive network. When adding a conductivity enhancer to reduce sheet resistance, it is difficult to simultaneously ensure the film-forming stability of the conductive layer and the substrate bonding performance. Therefore, a uniformly composed conductive layer cannot separately meet the adhesion and bending resistance requirements on the substrate side and the conductivity, flatness, and refractive index matching requirements on the functional layer side. After repeated bending or curved surface bonding, problems such as local resistance changes, coating separation, and increased interface reflection easily occur.

[0004] In view of this, the present invention proposes a method for preparing a flexible transparent conductive electrode based on PEDOT:PSS and its application, aiming to solve the problem that it is difficult for the homogeneous conductive layer of PEDOT:PSS to simultaneously achieve substrate bonding stability, bending resistance, conductivity and low reflectivity. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a flexible transparent conductive electrode based on PEDOT:PSS and its application, so as to solve the above-mentioned technical problems.

[0006] To achieve the above objectives, the present invention provides the following solution: On one hand, the method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS provided by the present invention includes the following steps: The surface of a flexible transparent substrate to be coated is activated to obtain an activated substrate; Using PEDOT:PSS aqueous dispersion as the main component, a polar conductivity enhancer, a flexible film-forming component, and a crosslinking component are added to prepare a first electrode coating solution and a second electrode coating solution. The contents of the flexible film-forming component and the crosslinking component in the first electrode coating solution relative to the PEDOT:PSS aqueous dispersion are 1.5 to 5.0 times and 2.0 to 8.0 times that in the second electrode coating solution, respectively. The contents of the polar conductivity enhancer in the second electrode coating solution relative to the PEDOT:PSS aqueous dispersion are 1.2 to 3.0 times that in the first electrode coating solution. The first electrode coating solution is applied to the activated substrate to form a first wet film. While the first wet film retains volatile components, the second electrode coating solution is applied to the first wet film to form a composite wet film with interlayer interdiffusion regions. The composite wet film is pre-dried and thermally cross-linked in sequence to form a composite conductive layer consisting of a flexible anchoring region adjacent to the activated substrate, a conductive matching region away from the activated substrate, and a compositional transition region located between the two. The composite conductive layer is rolled flat to obtain a flexible transparent conductive electrode, wherein the refractive index of the conductive matching region at a wavelength of 550 nm is 1.48 to 1.55.

[0007] Preferably, based on 100 parts by weight of PEDOT:PSS aqueous dispersion, the first electrode coating solution comprises 3-6 parts of polar conductivity enhancer, 2-8 parts of flexible film-forming component, 0.5-1.5 parts of crosslinking component, and 0.02-0.20 parts of wetting and leveling agent; the second electrode coating solution comprises 5-10 parts of polar conductivity enhancer, 0.2-3 parts of flexible film-forming component, 0.1-0.6 parts of crosslinking component, and 0.02-0.20 parts of wetting and leveling agent, wherein the flexible film-forming component and the crosslinking component are both added as an aqueous dispersion or aqueous solution with an effective ingredient content of 9%-11%.

[0008] Preferably, the polar conductive enhancer includes at least one of dimethyl sulfoxide, ethylene glycol, diethylene glycol, and glycerol; the flexible film-forming component includes at least one of aqueous polyurethane, polyethylene glycol, and polyvinyl alcohol; and the crosslinking component includes at least one of 3-glycidyl etheroxypropyltrimethoxysilane, polyethylene glycol diglycidyl ether, and water-dispersible blocked isocyanate.

[0009] Preferably, the flexible transparent substrate includes a polyethylene terephthalate substrate, a polyethylene naphthalate substrate, or a thermoplastic polyurethane substrate, with a thickness of 50–250 μm; the activation treatment includes corona treatment, oxygen plasma treatment, or ultraviolet ozone treatment, so that the surface tension of the surface to be coated reaches 38–52 mN / m.

[0010] Preferably, after the first wet film is formed, the second electrode coating solution is applied when the total mass of water and organic solvent in the first wet film accounts for 30% to 70% of the mass of the first wet film; the first electrode coating solution and the second electrode coating solution are applied by slit coating, microgravure coating, doctor blade coating or spin coating, respectively, and the nominal dry film thickness corresponding to the first electrode coating solution is 30 to 100 nm, and the nominal dry film thickness corresponding to the second electrode coating solution is 50 to 200 nm.

[0011] Preferably, the pre-drying temperature is 50-80℃ and the time is 1-5 min; the thermal cross-linking temperature is 100-130℃ and the time is 5-20 min; the roller pressing is carried out at 40-80℃ and 0.1-0.5 MPa pressure.

[0012] Preferably, the total thickness of the composite conductive layer is 80-300 nm, the surface roughness Ra is less than 5 nm, the sheet resistance is not greater than 150 Ω / □, and the average transmittance in the wavelength range of 400-700 nm is not less than 85%.

[0013] On the other hand, the present invention also provides a flexible transparent conductive electrode, comprising a flexible transparent substrate and a composite conductive layer disposed on one side of the flexible transparent substrate; the composite conductive layer comprises a flexible anchoring region, a compositional transition region and a conductive matching region connected in sequence, the flexible anchoring region being connected to the flexible transparent substrate, wherein the content of the flexible film-forming component and the crosslinking component in the flexible anchoring region is higher than that in the conductive matching region, the compositional transition region being formed by the interdiffusion of the coating liquid components forming the flexible anchoring region and the conductive matching region, and the refractive index of the conductive matching region at a wavelength of 550 nm being 1.48 to 1.55.

[0014] In another aspect, the present invention also provides a dimming film, comprising two flexible transparent conductive electrodes disposed opposite to each other, and a liquid crystal dimming functional layer sandwiched between the two flexible transparent conductive electrodes; the conductive matching regions of the two flexible transparent conductive electrodes are both oriented toward the liquid crystal dimming functional layer, and the refractive index difference between the conductive matching regions and the liquid crystal dimming functional layer at a wavelength of 550 nm is not greater than 0.08; the liquid crystal dimming functional layer comprises a polymer-dispersed liquid crystal composition or a dye liquid crystal composition.

[0015] In another aspect, the present invention also provides a curved dimming glass, comprising a first curved transparent substrate, a second curved transparent substrate and the dimming film described above, wherein the dimming film is disposed according to the curved shape of the first and second curved transparent substrates and is sandwiched between the two by an optical adhesive layer; at least one of the first and second curved transparent substrates has an anti-reflection layer on its outer surface, and the curved dimming glass is an automotive side window glass or an automotive sunroof glass.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention separately formulates a first electrode coating solution and a second electrode coating solution, such that the first electrode coating solution has a high content of flexible film-forming components and crosslinking components, and the second electrode coating solution has a high content of polar conductivity enhancer, thereby forming a flexible anchoring region and a conductivity matching region in the same composite conductive layer. The flexible anchoring region improves the bonding stability between the composite conductive layer and the flexible transparent substrate and withstands bending deformation, while the conductivity matching region maintains the continuity of the PEDOT conductive network, thereby reducing the mutual constraints that arise when a single formulation simultaneously meets different performance requirements.

[0017] 2. In this invention, a second electrode coating liquid is applied while the first wet film retains volatile components, allowing the two coating liquids to interdiffuse between layers and form a compositional transition region. This compositional transition region connects the flexible anchoring region and the conductive matching region, reducing abrupt compositional changes between the two regions and decreasing the possibility of separation or localized resistance changes along the interlayer during bending of the composite conductive layer.

[0018] 3. This invention removes some volatile components from the composite wet film through pre-drying, then fixes the structure of the flexible anchoring region, the transition region, and the conductive matching region through thermal cross-linking, and rolls the composite conductive layer to flatten it. This helps to reduce the residual solvent content and surface roughness, and reduce the impact of surface defects on conductive continuity and light propagation.

[0019] 4. In this invention, the refractive index of the conductive matching region at a wavelength of 550nm is controlled to be between 1.48 and 1.55, and the conductive matching region is positioned towards the liquid crystal dimming functional layer in the dimming film. This can reduce the refractive index difference between the transparent conductive electrode and the adjacent transparent dielectric layer, and reduce interface reflection within the multilayer structure.

[0020] 5. The flexible transparent conductive electrode formed by the present invention can be bent and set with the curved transparent substrate, and can be applied to automotive side window glass and automotive sunroof glass; by cooperating with the outer surface anti-reflection layer, it can simultaneously reduce the reflection of the internal interface of the dimming glass and the reflection of the outer surface. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] The PEDOT:PSS described in this invention is a conductive polymer composite formed from poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate; the PEDOT:PSS aqueous dispersion is a dispersion formed by dispersing the conductive polymer composite in water. Unless otherwise specified, the mass fraction of each component in the coating solution is based on 100 parts by mass of the PEDOT:PSS aqueous dispersion. The flexible film-forming component uses an aqueous dispersion or aqueous solution with an effective ingredient content of 9% to 11%, and the crosslinking component uses an aqueous solution or aqueous dispersion with an effective ingredient content of 9% to 11%, with the mass fraction calculated based on the actual added mass of the corresponding aqueous dispersion or aqueous solution. The first electrode coating solution and the second electrode coating solution use flexible film-forming components and crosslinking components with the same effective ingredient content. The first electrode coating solution and the second electrode coating solution use the same brand and batch of PEDOT:PSS aqueous dispersion to avoid the influence of differences in base solids content and the PEDOT to PSS ratio on the comparison of the two coating solutions.

[0023] The polar conductivity enhancer described in this invention can regulate the interaction between PEDOT and PSS and promote PEDOT segment rearrangement during film formation. It includes one or more of dimethyl sulfoxide, ethylene glycol, diethylene glycol, and glycerol. When dimethyl sulfoxide is combined with glycerol, dimethyl sulfoxide primarily promotes conductive network rearrangement during pre-drying and thermal crosslinking, while glycerol, as a polar component with a higher boiling point, is partially retained in the composite conductive layer, thus balancing conductivity enhancement and flexural deformation adaptability.

[0024] The flexible film-forming component includes aqueous polyurethane, polyethylene glycol, or polyvinyl alcohol. This component is distributed between PEDOT:PSS particles, improving the coating's deformability without completely blocking contact between conductive particles. The crosslinking component includes 3-glycidyl etheroxypropyltrimethoxysilane, polyethylene glycol diglycidyl ether, or a water-dispersible blocked isocyanate. During heat treatment, the crosslinking component forms a crosslinked structure, restricting the migration of PEDOT and the flexible film-forming component during subsequent use.

[0025] The flexible anchoring region, compositional transition region, and conductive matching region described in this invention do not necessarily have clearly defined layered structures. The flexible anchoring region is the area adjacent to the flexible transparent substrate where the flexible film-forming component and crosslinking component are relatively abundant; the conductive matching region is the area away from the flexible transparent substrate, formed by the second electrode coating liquid, where the content of the flexible film-forming component and crosslinking component is relatively low; the compositional transition region is a continuous compositional change region formed by the mutual diffusion of the two coating liquids in the wet film state.

[0026] I. Preparation of Electrode Coating Solution Before preparing the electrode coating solution, stir the PEDOT:PSS aqueous dispersion at 200-400 rpm for 20-40 minutes at 20-30°C to restore the dispersion to a homogeneous state. Then, while maintaining stirring, slowly add the polar conductivity enhancer and continue stirring for 20-40 minutes; then add the flexible film-forming component and stir for 30-60 minutes; finally, add the crosslinking component and wetting and leveling agent and stir for 30-60 minutes.

[0027] The crosslinking component is added after the other components are evenly dispersed to reduce premature crosslinking during the storage of the coating solution. The prepared coating solution is filtered through a filter membrane with a pore size of 0.45–1.0 μm and degassed under a vacuum of -0.06–-0.09 MPa for 5–15 min. The coating solution with the added crosslinking component is sealed and stored at 20–25 °C, and coating is preferably completed within 8 h.

[0028] The contents of the flexible film-forming component and the crosslinking component in the first electrode coating solution are 1.5 to 5.0 times and 2.0 to 8.0 times that of the second electrode coating solution, respectively; the content of the polar conductivity enhancer in the second electrode coating solution is 1.2 to 3.0 times that of the first electrode coating solution. These content relationships are determined based on the actual added mass of the corresponding aqueous materials for the flexible film-forming component and the crosslinking component, and both the first and second electrode coating solutions use the same content of effective ingredients in the flexible film-forming component and the crosslinking component.

[0029] II. Activation Treatment of Flexible Transparent Substrates The flexible transparent substrate can be polyethylene terephthalate film, polyethylene naphthalate film, or thermoplastic polyurethane film, with a thickness of 50–250 μm.

[0030] The flexible transparent substrate is cleaned sequentially with deionized water and isopropanol to remove surface particles, oil, and release agent, and then dried at 60–80°C for 5–15 minutes. After drying, the flexible transparent substrate undergoes corona treatment, oxygen plasma treatment, or ultraviolet ozone treatment. Following activation treatment, the surface tension of the surface to be coated is determined using dyne solution or contact angle testing, ensuring a surface tension of 38–52 mN / m.

[0031] When the surface tension is below 38 mN / m, the PEDOT:PSS aqueous coating solution is prone to pinholes or localized dewetting; when the surface tension is too high and the activation time is too long, the surface of the flexible transparent substrate may be over-oxidized. Therefore, it is preferable to apply the first electrode coating solution within 2 hours after the activation treatment is completed.

[0032] III. Formation of Composite Conductive Layer The first electrode coating solution is applied to the activated substrate by slit coating, microgravure coating, doctor blade coating, or spin coating to form a first wet film. After the first wet film has leveled or partially evaporated for a short time, the second electrode coating solution is applied while it still retains water and organic solvents.

[0033] The mass percentage of volatile components in the first wet film can be determined by weighing. Specifically, a witness sample with the same material and area as the substrate for the final coating is taken, and the mass of the substrate, the mass immediately after the first coating, the mass after different evaporation times, and the mass after the first wet film is completely dry are recorded. The water and organic solvent content in the current first wet film is determined based on the difference between these masses. When the total mass of water and organic solvents accounts for 30% to 70% of the mass of the first wet film, a second coating is applied. In continuous production, the volatile component content of the first wet film can be measured using a near-infrared moisture detector, and calibrated using a weighing method.

[0034] When the second electrode coating solution comes into contact with the first wet film, which is not yet fully dried, the PEDOT:PSS particles, flexible film-forming components, crosslinking components, and polar conductivity enhancers in both coating solutions undergo limited diffusion in the contact area. When the volatile component content of the first wet film is less than 30%, the diffusion between the two layers is insufficient, and a distinct interlayer interface is easily formed; when it is higher than 70%, the second electrode coating solution easily disturbs the first wet film, causing changes in the thickness of the first wet film.

[0035] After forming the composite wet film, it is first pre-dried at 50–80°C for 1–5 min to evaporate most of the water and low-boiling-point organic solvents; then it is thermally cross-linked at 100–130°C for 5–20 min to allow the cross-linked components to react and fix the composition distribution in the composite conductive layer. After thermal cross-linking, the composite conductive layer is cooled to 40–80°C and rolled flat under a pressure of 0.1–0.5 MPa.

[0036] By controlling the solid content, coating gap, and coating amount per unit area of ​​the first and second electrode coating solutions, the nominal dry film thickness corresponding to the first electrode coating solution is 30–100 nm, the nominal dry film thickness corresponding to the second electrode coating solution is 50–200 nm, and the total thickness of the composite conductive layer is 80–300 nm. The transition region is located within the overlap area of ​​the corresponding regions of the two nominal dry films and does not additionally increase the total thickness of the composite conductive layer.

[0037] In this embodiment, the PEDOT:PSS aqueous dispersion has a solid content of 1.2%, and the first electrode coating solution and the second electrode coating solution use PEDOT:PSS aqueous dispersion with the same solid content.

[0038] Example 1 In this embodiment, an optical-grade PET film with a thickness of 125 μm is used as a flexible transparent substrate.

[0039] Based on 100 parts by weight of PEDOT:PSS aqueous dispersion, the first electrode coating solution includes 3.2 parts of dimethyl sulfoxide, 0.8 parts of glycerol, 4 parts of nonionic aqueous polyurethane dispersion with a solid content of 10%, 1 part of 3-glycidyl etheroxypropyltrimethoxysilane aqueous solution with an active ingredient content of 10%, and 0.08 parts of nonionic wetting and leveling agent. The total amount of polar conductivity enhancer in the first electrode coating solution is 4 parts.

[0040] Based on 100 parts by weight of PEDOT:PSS aqueous dispersion, the second electrode coating solution includes 6.4 parts dimethyl sulfoxide, 1.6 parts glycerol, 1.5 parts nonionic aqueous polyurethane dispersion with a solid content of 10%, 0.25 parts 3-glycidyl etheroxypropyltrimethoxysilane aqueous solution with an active ingredient content of 10%, and 0.08 parts nonionic wetting and leveling agent. The total amount of polar conductivity enhancer in the second electrode coating solution is 8 parts.

[0041] The content of aqueous polyurethane in the first electrode coating solution is 2.67 times that in the second electrode coating solution, and the content of crosslinking components is 4 times that in the second electrode coating solution; the content of polar conductivity enhancer in the second electrode coating solution is 2 times that in the first electrode coating solution.

[0042] The PET film was cleaned sequentially with deionized water and isopropanol, dried at 70°C for 10 minutes, and then treated with oxygen plasma for 60 seconds to achieve a surface tension of 44 mN / m on the surface to be coated.

[0043] The first electrode coating solution is applied to the activated surface of the PET film using a slit coating method, and the nominal dry film thickness corresponding to the dried first electrode coating solution is controlled to be 60 nm. The first wet film is leveled and partially evaporated. When the total mass of water and organic solvent in the first wet film accounts for 50% of the mass of the first wet film, the second electrode coating solution is applied using a second slit coating head, and the nominal dry film thickness corresponding to the dried second electrode coating solution is controlled to be 120 nm.

[0044] The formed composite wet film was pre-dried at 65°C for 3 min, and then thermally crosslinked at 120°C for 12 min. After thermal crosslinking, it was cooled to 60°C and rolled once under a pressure of 0.25 MPa to obtain a flexible transparent conductive electrode with a total composite conductive layer thickness of approximately 180 nm.

[0045] In this embodiment, the second electrode coating solution is applied before the first wet film is completely dry, and the two coating solutions interdiffusion occurs in the contact area. After thermal crosslinking, a flexible anchoring region is formed on the side adjacent to the PET film, and a conductive matching region is formed on the side away from the PET film, with a composition transition region of continuously changing composition formed between the two.

[0046] Example 2 In this embodiment, an optical-grade PEN film with a thickness of 100 μm is used as a flexible transparent substrate.

[0047] The first electrode coating solution includes 100 parts of PEDOT:PSS aqueous dispersion, 3 parts of ethylene glycol, 2 parts of diethylene glycol, 4.5 parts of polyethylene glycol aqueous solution with an effective ingredient content of 10%, 1.2 parts of polyethylene glycol diglycidyl ether aqueous solution with an effective ingredient content of 10%, and 0.05 parts of wetting and leveling agent.

[0048] The second electrode coating solution includes 100 parts of PEDOT:PSS aqueous dispersion, 5 parts of ethylene glycol, 3 parts of diethylene glycol, 1.5 parts of polyethylene glycol aqueous solution with an effective ingredient content of 10%, 0.3 parts of polyethylene glycol diglycidyl ether aqueous solution with an effective ingredient content of 10%, and 0.05 parts of wetting and leveling agent.

[0049] The content of polyethylene glycol in the first electrode coating solution is 3 times that in the second electrode coating solution, and the content of crosslinking components is 4 times that in the second electrode coating solution; the content of polar conductivity enhancer in the second electrode coating solution is 1.6 times that in the first electrode coating solution.

[0050] After cleaning and drying, the PEN film undergoes corona treatment to achieve a surface tension of 46 mN / m on the surface to be coated. A first electrode coating solution is applied using a doctor blade coating method, controlling the amount of the first electrode coating solution applied per unit area to achieve a dry film thickness of 80 nm. When the total mass of water and organic solvent in the first wet film accounts for 40% of the first wet film's mass, a second electrode coating solution is applied, controlling the amount of the second electrode coating solution applied per unit area to achieve a dry film thickness of 150 nm.

[0051] The composite wet film is pre-dried at 70°C for 4 minutes, thermally cross-linked at 125°C for 15 minutes, and then rolled flat at 70°C and 0.30 MPa pressure to obtain a flexible transparent conductive electrode with a total composite conductive layer thickness of approximately 230 nm. The compositional transition region is located within the range where the first electrode coating liquid and the second electrode coating liquid interdiffusion occur, and is included in the total thickness of the composite conductive layer.

[0052] Example 3 This embodiment illustrates a continuous fabrication method for flexible transparent conductive electrodes.

[0053] A PET roll with a width of 300mm and a thickness of 188μm is used as a flexible transparent substrate. A cleaning unit, a corona treatment unit, a first slit coating head, a volatile component detection unit, a second slit coating head, a pre-drying unit, a thermal crosslinking unit, and a hot rolling unit are arranged sequentially along the roll conveying direction.

[0054] The first and second electrode coating solutions adopted the formulations of Example 1. The PET roll material, after corona treatment, had a surface tension of 42–46 mN / m. A first slit coating head formed a first wet film on the surface of the PET roll material, which passed through a short-range evaporation zone at a temperature of 50–60°C. When the near-infrared moisture detection device detected that the volatile component content in the first wet film reached 45%–55%, the second slit coating head applied the second electrode coating solution onto the first wet film.

[0055] The composite wet film enters a pre-drying zone at 60–70°C for 3 minutes; then it enters a thermal cross-linking zone at 115–125°C for 12 minutes; and then passes through a hot rolling unit at 55–65°C and 0.20–0.30 MPa. By adjusting the roll conveying speed and the length of each processing zone, the roll reaches the corresponding residence time in each processing zone, controlling the coating amount per unit area of ​​the first and second electrode coating liquids. This results in a dry film thickness of approximately 65 nm for the first electrode coating liquid and approximately 125 nm for the second electrode coating liquid, ultimately forming a composite conductive layer with a total thickness of approximately 190 nm. The transition zone is located within the interdiffusion range of the two electrode coating liquids and is included in the total thickness of the composite conductive layer. Finally, the roll is wound up to obtain a flexible transparent conductive electrode roll.

[0056] IV. Examples of Preparation of Dimming Film Take two flexible transparent conductive electrodes prepared in Example 1, set conductive silver paste busbars at the edge of the conductive matching area of ​​each electrode, and connect copper foil leads to the conductive silver paste busbars.

[0057] The first flexible transparent conductive electrode is placed with its conductive matching region facing upwards. A liquid crystal dimming precursor is coated on it, and the thickness of the liquid crystal dimming functional layer is controlled by spacer particles or spacers. The conductive matching region of the second flexible transparent conductive electrode is then placed facing the liquid crystal dimming precursor, so that the two flexible transparent conductive electrodes are positioned opposite each other.

[0058] The liquid crystal dimming precursor can be a polymer-dispersed liquid crystal precursor or a dye liquid crystal precursor containing dichroic dyes. Spacer particles are used to control the thickness of the liquid crystal dimming functional layer to 20 μm. The stacked liquid crystal dimming precursor is irradiated under ultraviolet light with a wavelength of 365 nm and an irradiance of 8 mW / cm² for 120 s to cure the liquid crystal dimming precursor and form the liquid crystal dimming functional layer. The above curing conditions are only standard curing conditions used uniformly in all embodiments and comparative examples.

[0059] The dimming film obtained includes, from one side to the other, a first flexible transparent substrate, a first flexible anchoring region, a first composition transition region, a first conductive matching region, a liquid crystal dimming functional layer, a second conductive matching region, a second composition transition region, a second flexible anchoring region, and a second flexible transparent substrate.

[0060] Both conductive matching regions face the liquid crystal dimming functional layer. The composition ratio of the second electrode coating liquid is selected based on the refractive index of the liquid crystal dimming functional layer at a wavelength of 550 nm, so that the difference in refractive index between the conductive matching region and the liquid crystal dimming functional layer at a wavelength of 550 nm is not greater than 0.08.

[0061] V. Examples of Preparation of Curved Smart Glass A first curved transparent substrate and a second curved transparent substrate are provided, wherein the first curved transparent substrate and the second curved transparent substrate are automotive glass with mutually matching curvatures. An anti-reflective layer is disposed on the outer surface of at least one curved transparent substrate.

[0062] A first optical adhesive layer is formed on the inner surface of a first curved transparent substrate. The dimming film is then attached segment by segment to the first optical adhesive layer along the curved surface of the first curved transparent substrate, causing the flexible transparent conductive electrode in the dimming film to bend along with the curved transparent substrate. Subsequently, a second optical adhesive layer is formed on the side of the dimming film facing away from the first curved transparent substrate, and covers the second curved transparent substrate.

[0063] During the bonding process, pressure is gradually applied from the center area of ​​the dimming film to the edge area to expel interlayer air, and then vacuum bonding or pressure bonding is performed according to the curing conditions of the optical adhesive layer. The leads of the two flexible transparent conductive electrodes are led out from the edge of the curved dimming glass, and the lead outlets and the periphery of the dimming film are insulated and sealed.

[0064] The resulting curved dimming glass can be used as automotive side window glass or automotive sunroof glass. The flexible anchoring area withstands the bending deformation generated when the dimming film is bonded to the curved transparent substrate, and the conductive matching area faces the liquid crystal dimming functional layer, forming a transition area connecting the flexible anchoring area and the conductive matching area.

[0065] Comparative Example 1 Comparative Example 1 used a uniformly composed PEDOT:PSS electrode coating solution. Based on 100 parts of PEDOT:PSS aqueous dispersion, 6.7 parts of a polar conductivity enhancer, 2.3 parts of a 10% solids content nonionic aqueous polyurethane dispersion, 0.5 parts of a 10% effective ingredient aqueous solution of 3-glycidyl etheroxypropyltrimethoxysilane, and 0.08 parts of a wetting and leveling agent were added. This coating solution was applied in one pass to the same PET film as in Example 1, controlling the total thickness of the conductive layer after drying to 180 nm, and using the same pre-drying, thermal crosslinking, and rolling conditions as in Example 1.

[0066] Comparative Example 2 Comparative Example 2 used the same first and second electrode coating solutions as Example 1, but after the first electrode coating solution was applied, it was first dried at 65°C for 5 minutes and then heat-treated at 120°C for 12 minutes to ensure the first coating was completely dry before applying the second electrode coating solution. After the second coating was applied, it underwent pre-drying, thermal crosslinking, and rolling according to the conditions of Example 1. This comparative example was used to compare the differences between wet-on-wet coating and layered coating after complete drying.

[0067] Comparative Example 3 uses an ITO-PET transparent conductive film with the same thickness as the PET film in Example 1, and cuts it to the same size to compare the change in sheet resistance before and after bending, visible light reflection, and conductivity continuity after curved surface bonding.

[0068] VI. Testing Methods 1. The thickness of the composite conductive layer was measured using a step gauge, cross-sectional scanning electron microscope, or ellipsometry. Multiple locations were selected in both the length and width directions of the sample, and the average value of the measurement results was taken.

[0069] 2. Surface roughness was measured using atomic force microscopy. At least three regions were selected on the conductive matching area surface for scanning, with a scanning range of 5μm × 5μm. The arithmetic mean roughness Ra was calculated based on the height data.

[0070] 3. Sheet resistance was measured using a four-probe sheet resistance tester. At least nine measurement positions were selected at the center, four corners, and the middle of each side of the sample. The sheet resistance at each position was recorded, and the average value and dispersion were calculated.

[0071] 4. Visible light transmittance was measured using a UV-Vis spectrophotometer. The test object included a complete electrode consisting of a flexible transparent substrate and a composite conductive layer. The transmittance was continuously scanned within the wavelength range of 400–700 nm and the average transmittance was calculated.

[0072] 5. Refractive index was measured using a spectroscopic ellipsometer. A calibration sample with a conductive matching region was prepared on the same substrate as the final sample using the same process. An optical fitting model was established based on the thickness of the conductive matching region to obtain the refractive index at 550 nm wavelength. When anisotropy was significant, the in-plane refractive index and the refractive index along the thickness direction were recorded separately, and the refractive index matching relationship was evaluated using the refractive index corresponding to the actual incident light direction.

[0073] 6. The compositional distribution of the composite conductive layer was determined using X-ray photoelectron spectroscopy depth analysis or time-of-flight secondary ion mass spectrometry depth analysis. Based on the changes in characteristic signals of the crosslinked components, flexible film-forming components, and PEDOT with depth, the flexible anchoring region, compositional transition region, and conductive matching region were identified. The depth range in which the characteristic signal continuously changes from the flexible anchoring region to the conductive matching region was defined as the compositional transition region.

[0074] 7. Adhesion stability was evaluated using cross-cut adhesion and tape peeling methods. After crossing the composite conductive layer, tape with a specified adhesion was applied and peeled off at a specified angle and speed. The composite conductive layer was observed to see if it detached, and the sheet resistance was measured before and after the test.

[0075] 8. Bending resistance was tested using a reciprocating bending device. The sample was repeatedly bent around a bending axis with a radius of 5 mm, with the composite conductive layer on the outside and inside of the bend, respectively. After a set number of cycles, the sheet resistance was measured. The rate of change of sheet resistance before and after the test and the presence of cracks in the conductive layer were used as evaluation indicators.

[0076] 9. The reflectance of the dimming film and curved dimming glass was measured using a spectrophotometer with an integrating sphere. The reflectance in the wavelength range of 400–700 nm was measured in both the power-off and power-on transparent states. The examples and comparative examples were compared under the same glass, liquid crystal dimming functional layer, optical adhesive layer, and test conditions.

[0077] 10. Environmental stability can be evaluated through high temperature and high humidity tests. Place the sample in an environment with a temperature of 85℃ and a relative humidity of 85%, remove the sample at different test times, and measure the sheet resistance, transmittance, and adhesion status after restoring to room temperature.

[0078] By comparing Examples 1-3 with Comparative Examples 1-3, the effects of differentiated formulation, wet-on-wet coating, compositional transition zone, and PEDOT:PSS electrode replacement of ITO electrode on adhesion stability, conductivity, flexural strength, and optical properties can be examined.

[0079] Performance Tests and Results To verify the conductivity, optical properties, interfacial bonding properties, and bending stability of the composite conductive layer described in this invention, samples prepared in Examples 1-3 and Comparative Examples 1-3 were tested.

[0080] In Comparative Example 1, the same PEDOT:PSS aqueous dispersion, polar conductive enhancer, flexible film-forming component and crosslinking component as in Example 1 were used, and the total amount of each component and the total thickness of the conductive layer were basically the same as in Example 1. However, the components were mixed once to form a single electrode coating solution, and a homogeneous conductive layer was formed by one-time coating.

[0081] Comparative Example 2 uses the same first electrode coating solution and second electrode coating solution as Example 1, but after the first wet film is completely dried and treated at 120°C for 12 min, the second electrode coating solution is applied to prevent the formation of an obvious wet interdiffusion region between the first conductive layer and the second conductive layer.

[0082] Comparative Example 3 uses a commercial ITO-PET transparent conductive film with a thickness of 125 μm, wherein the ITO layer has a thickness of 120 nm.

[0083] Five parallel samples were prepared for each group. Unless otherwise specified, the data in the table are the average of the five parallel samples, and "±" after the value indicates the standard deviation.

[0084] I. Testing Methods 1. The thickness of the conductive layer was determined using a profilometer and a spectroscopic ellipsometry. Five locations were selected for measurement for each sample.

[0085] 2. Under conditions of 25℃ and 50% relative humidity, the sheet resistance of the samples was measured using a four-probe sheet resistance meter. The center position and the four corner positions of each sample were measured separately.

[0086] 3. The transmittance of the sample in the wavelength range of 400–700 nm was measured using an ultraviolet-visible spectrophotometer with an integrating sphere, and the average transmittance was calculated according to a wavelength interval of 5 nm.

[0087] 4. The surface roughness Ra of the composite conductive layer was measured by scanning a 5μm×5μm area using an atomic force microscope.

[0088] 5. The haze of the sample was measured using a haze meter.

[0089] 6. The refractive index of the conductive matching region or the surface layer of the conductive layer at a wavelength of 550 nm was determined using a spectroscopic ellipsometry. For the composite conductive layer, a multilayer optical model was used to fit the flexible anchoring region, the compositional transition region, and the conductive matching region respectively.

[0090] 7. Evaluate the adhesion of the conductive layer according to the cross-cut test method described in ASTM D3359. The adhesion from high to low is recorded as 5B, 4B, 3B, 2B, 1B and 0B.

[0091] 8. The bending test uses a 5mm bending radius, with the conductive layer facing outwards. It involves 1000 reciprocating bends at a frequency of 30 bends / min. The sheet resistance is measured before and after each bend, and the rate of change of sheet resistance is calculated using the following formula: Rate of change of sheet resistance = (Sheet resistance after bending - Sheet resistance before bending) / Sheet resistance before bending × 100%.

[0092] 9. Place the sample in an environment with a temperature of 85℃ and a relative humidity of 85% for 500 hours, and determine the sheet resistance and adhesion before and after the damp heat treatment.

[0093] II. Electrical, optical and surface properties are shown in Table 1.

[0094] Table 1 As can be seen from the results in the table, the sheet resistance of the composite conductive layer prepared in Examples 1 to 3 is 89 to 108 Ω / □, the average transmittance in the wavelength range of 400 to 700 nm is 88.8% to 89.6%, and the surface roughness Ra is 2.2 to 2.7 nm, thus meeting the requirements for conductivity, transmittance and flatness.

[0095] Although Comparative Example 1 has essentially the same total component dosage and conductive layer thickness as Example 1, its sheet resistance increases to 128 Ω / □ because the flexible film-forming component and crosslinking component are uniformly distributed throughout the conductive layer, hindering the formation of the PEDOT conductive network. Comparative Example 2, while having a lower sheet resistance, suffers from reduced wetting and leveling of the second electrode coating solution on the surface of the first conductive layer after the first conductive layer is completely dry, leading to increased surface roughness and haze.

[0096] The ITO conductive layer of Comparative Example 3 has a lower initial sheet resistance, but its refractive index at 550 nm wavelength is significantly higher than that of the conductive matching region of Examples 1-3.

[0097] III. Adhesion, bending performance and resistance to damp heat are shown in Table 2.

[0098] Table 2 In Examples 1-3, the sheet resistance change rate after 1000 bends did not exceed 7.4%, and the adhesion after bending still reached 5B, indicating that the flexible anchoring area set adjacent to the flexible transparent substrate can improve the bonding strength between the composite conductive layer and the flexible transparent substrate, and buffer the stress generated during bending.

[0099] In Comparative Example 1, the homogeneous conductive layer cannot simultaneously form a flexible anchoring region with relatively rich cross-linked components and a conductive matching region with relatively rich conductive reinforcing agents, resulting in localized microcracks and interfacial delamination during bending. In Comparative Example 2, the first and second conductive layers lack a continuously varying interdiffusion region, and after bending, localized delamination mainly occurs between the two layers.

[0100] The ITO conductive layer in Comparative Example 3 has good initial conductivity and resistance to damp heat, but obvious cracks appeared after 1000 bends, and its sheet resistance change rate reached 184%, indicating that the ITO conductive layer is not suitable for application scenarios that require repeated bending or curved surface bonding.

[0101] IV. The depth-direction composition analysis of the composite conductive layer is shown in Table 3.

[0102] The composite conductive layer of Example 1 was analyzed in depth direction using time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy. The characteristic signals of the flexible film-forming component and the crosslinking component were characterized by nitrogen-containing urethane fragments and silicon-containing siloxane fragments, respectively. The characteristic ion signals of each component were normalized to 1.00 based on their maximum signal intensity in the composite conductive layer.

[0103] Table 3 Depth-direction analysis results show that the flexible film-forming components and cross-linking components gradually decrease from the flexible transparent substrate side towards the surface of the composite conductive layer, while the peak area ratio of PEDOT sulfur to PSS sulfur gradually increases. A continuous compositional variation region with a thickness of approximately 34±5 nm was detected between the flexible anchoring region and the conductive matching region. No abrupt changes in the compositional signal were observed, indicating that applying the second electrode coating liquid while the first wet film retains volatile components can form a compositional transition region through wet interdiffusion.

[0104] V. Performance tests of the dimming film are shown in Table 4.

[0105] PDLC dimming films with identical structures were prepared using the flexible transparent conductive electrodes of Examples 1-3 and Comparative Examples 1-3, respectively. Except for the different transparent conductive electrodes, the liquid crystal composition, functional layer thickness, curing conditions, and sealing conditions of each dimming film were identical.

[0106] The PDLC functional layer has an equivalent refractive index of 1.53 at 550 nm in the electrically transparent state. During testing, an AC voltage of 1 kHz was applied to the dimming film, and the transmittance, reflectance, and haze in the electrically transparent state were measured at 60 V. The average reflectance is the spectral average value within the wavelength range of 400–700 nm.

[0107] Table 4 In Examples 1-3, the refractive index difference between the conductive matching region and the PDLC functional layer does not exceed 0.03, reducing the average reflectivity under energized conditions to 8.8%-9.0%. Compared with Comparative Example 3, which uses an ITO transparent electrode, the average reflectivity of Examples 1-3 is reduced by 3.9, 3.7, and 3.8 percentage points, respectively, while the average transmittance under energized conditions is increased by 2.9-4.0 percentage points.

[0108] Examples 1-3 and Comparative Example 1 all use PEDOT:PSS material, and therefore all have a certain refractive index matching effect. However, Comparative Example 1 lacks functional partitions formed along the thickness direction, and its bending stability and resistance to damp heat are significantly lower than those of Examples 1-3. This shows that the technical effect of the present invention does not only come from replacing ITO with PEDOT:PSS, but also from the synergistic setting of the flexible anchoring area, the transition area, and the conductive matching area.

[0109] VI. Performance tests of curved smart glass are shown in Table 5.

[0110] Test terminals were placed at opposite ends of each flexible transparent conductive electrode. The resistance between the same two test terminals was measured at 25°C before and after the curved surfaces were bonded together. The average resistance change rate of the two flexible transparent conductive electrodes was taken as the electrode circuit resistance change rate before and after the curved surfaces were bonded together. Dimming films made using the electrodes of Example 1, Comparative Example 1, and Comparative Example 3 were sandwiched between two curved glass substrates using the same optical adhesive layer. The minimum radius of curvature of the curved glass was 300 mm, and the outer surface of the outer curved glass was provided with the same anti-reflective layer.

[0111] Table 5 The results show that after the dimming film of Example 1 is bonded to curved glass, the change rate of its electrode circuit resistance is 2.3%, which is lower than that of Comparative Example 1 and Comparative Example 3 using ITO electrodes, indicating that the composite conductive layer has good stability when bonded to curved surfaces. Meanwhile, the average reflectivity of Example 1 in the energized state is 3.7 percentage points lower than that of Comparative Example 3, indicating that it is suitable for curved dimming glass such as automotive side windows and sunroofs.

[0112] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit of the present invention should fall within the protection scope defined by the present invention.

Claims

1. A method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS, characterized in that, Includes the following steps: The surface of a flexible transparent substrate to be coated is activated to obtain an activated substrate; Using PEDOT:PSS aqueous dispersion as the main component, a polar conductivity enhancer, a flexible film-forming component, and a crosslinking component are added to prepare a first electrode coating solution and a second electrode coating solution. The contents of the flexible film-forming component and the crosslinking component in the first electrode coating solution relative to the PEDOT:PSS aqueous dispersion are 1.5 to 5.0 times and 2.0 to 8.0 times that in the second electrode coating solution, respectively. The contents of the polar conductivity enhancer in the second electrode coating solution relative to the PEDOT:PSS aqueous dispersion are 1.2 to 3.0 times that in the first electrode coating solution. The first electrode coating solution is applied to the activated substrate to form a first wet film. While the first wet film retains volatile components, the second electrode coating solution is applied to the first wet film to form a composite wet film with interlayer interdiffusion regions. The composite wet film is pre-dried and thermally cross-linked in sequence to form a composite conductive layer consisting of a flexible anchoring region adjacent to the activated substrate, a conductive matching region away from the activated substrate, and a compositional transition region located between the two. The composite conductive layer is rolled flat to obtain a flexible transparent conductive electrode, wherein the refractive index of the conductive matching region at a wavelength of 550 nm is 1.48 to 1.

55.

2. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 1, characterized in that, Based on 100 parts by weight of PEDOT:PSS aqueous dispersion, the first electrode coating solution includes 3-6 parts of polar conductivity enhancer, 2-8 parts of flexible film-forming component, 0.5-1.5 parts of crosslinking component and 0.02-0.20 parts of wetting and leveling agent; The second electrode coating solution includes 5-10 parts of a polar conductivity enhancer, 0.2-3 parts of a flexible film-forming component, 0.1-0.6 parts of a crosslinking component, and 0.02-0.20 parts of a wetting and leveling agent. The flexible film-forming component and the crosslinking component are added as an aqueous dispersion or aqueous solution with an effective ingredient content of 9%-11%.

3. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 2, characterized in that, The polar conductive enhancer includes at least one of dimethyl sulfoxide, ethylene glycol, diethylene glycol, and glycerol; the flexible film-forming component includes at least one of aqueous polyurethane, polyethylene glycol, and polyvinyl alcohol; the crosslinking component includes at least one of 3-glycidyl etheroxypropyltrimethoxysilane, polyethylene glycol diglycidyl ether, and water-dispersible blocked isocyanate.

4. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 1, characterized in that, The flexible transparent substrate includes polyethylene terephthalate substrate, polyethylene naphthalate substrate, or thermoplastic polyurethane substrate, with a thickness of 50-250 μm; the activation treatment includes corona treatment, oxygen plasma treatment, or ultraviolet ozone treatment, so that the surface tension of the surface to be coated reaches 38-52 mN / m.

5. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 1, characterized in that, After the first wet film is formed, the second electrode coating solution is applied when the total mass of water and organic solvent in the first wet film accounts for 30% to 70% of the mass of the first wet film. The first electrode coating solution and the second electrode coating solution are applied by slit coating, microgravure coating, doctor blade coating or spin coating, respectively. The nominal dry film thickness corresponding to the first electrode coating solution is 30 to 100 nm, and the nominal dry film thickness corresponding to the second electrode coating solution is 50 to 200 nm.

6. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 1, characterized in that, The pre-drying temperature is 50–80°C and the time is 1–5 min; the thermal cross-linking temperature is 100–130°C and the time is 5–20 min; the roller pressing and leveling are carried out at 40–80°C and 0.1–0.5 MPa pressure.

7. The method for fabricating a flexible transparent conductive electrode based on PEDOT:PSS according to claim 1, characterized in that, The total thickness of the composite conductive layer is 80–300 nm, the surface roughness Ra is less than 5 nm, the sheet resistance is not greater than 150 Ω / □, and the average transmittance in the wavelength range of 400–700 nm is not less than 85%.

8. A flexible transparent conductive electrode, characterized in that, The invention includes a flexible transparent substrate and a composite conductive layer disposed on one side of the flexible transparent substrate. The composite conductive layer includes a flexible anchoring region, a compositional transition region, and a conductive matching region connected in sequence. The flexible anchoring region is connected to the flexible transparent substrate. The content of the flexible film-forming component and the crosslinking component in the flexible anchoring region is higher than that in the conductive matching region. The compositional transition region is formed by the interdiffusion of the coating liquid components that form the flexible anchoring region and the conductive matching region. The refractive index of the conductive matching region at a wavelength of 550 nm is 1.48 to 1.

55.

9. A dimming film, characterized in that, The device includes two flexible transparent conductive electrodes as described in claim 8, arranged opposite to each other, and a liquid crystal dimming functional layer sandwiched between the two flexible transparent conductive electrodes; the conductive matching regions of the two flexible transparent conductive electrodes are both oriented towards the liquid crystal dimming functional layer, and the refractive index difference between the conductive matching regions and the liquid crystal dimming functional layer at a wavelength of 550 nm is not greater than 0.08; the liquid crystal dimming functional layer comprises a polymer-dispersed liquid crystal composition or a dye liquid crystal composition.

10. A curved dimming glass, characterized in that, The device includes a first curved transparent substrate, a second curved transparent substrate, and the dimming film as described in claim 9. The dimming film is configured according to the curved shape of the first and second curved transparent substrates and is sandwiched between them by an optical adhesive layer. At least one of the first and second curved transparent substrates has an anti-reflection layer on its outer surface. The curved dimming glass is an automotive side window glass or an automotive sunroof glass.

Citation Information

Patent Citations

  • Intelligent light adjusting film

    CN107817618A